Assessing functional disability in individuals with MCI and dementia: Psychosocial factors and environmental design / Living with dementia and quality of life. (7th December 2020) - Umucu, Emre; Wyman, Mary F; Lee, Beatrice; Zuelsdorff, Megan; Lambrou, Nickolas H; Johnson, Adrienne L; Bouges, Shenikqua; James, Taryn T; Salazar, Hector; Simó, Carola A Ferrer; Carter, Fabu P; Asthana, Sanjay; et al.
Abstract: Background: Mild cognitive impairment (MCI) and dementia are among the most disabling conditions. Patients with MCI and dementia may experience difficulties in executing instrumental activities of daily living (IADL), resulting in distress for patients and families. Measuring and understanding abilities to execute IADL is important to understand how MCI and dementia impacts patients' functioning. We explored the factor structure of the Functional Activities Questionnaire as a measure of functional disability in a sample with MCI and dementia. Methods: Participants were 198 enrollees in the Wisconsin ADRC who had MCI, and dementia. Not applicable responses were counted as missing data, resulting in 98 participants in main analyses. The majority of participants were male (61.1%) and Caucasian (88.4%). Average age at baseline was 73.76 ( SD =8.90). We conducted the following analysis: exploratory factor analysis (EFA), reliability analysis, correlation analysis, and Mann‐Whitney U test. Results: The Kaiser–Meyer–Olkin (KMO) measure of sampling adequacy was .89, and the Barlett's test of sphericity was significant, χ 2 (45, N =98)=717.24, p <.001, indicating suitability for factor analysis. Kaiser–Guttman's criterion and Cattell's scree test both indicated a single‐factor measurement structure, accounting for 64% of the total variance. The Cronbach's alpha was found to be .94 for the FAQ. Functional disability was positively correlated with neuropsychiatric symptoms (r=.43, p <.001), CDR global score (r=.79, p <.001), and lack of independence (r=.66, p <.001). A Mann‐Whitney U test showed that individuals with dementia had significantly higher levels of functional disability than those with MCI (U=214.00, p <.001). Conclusion: The FAQ was found to be a unidimensional, reliable, and valid measure of functional disability. Participants with higher scores on the FAQ endorsed greater levels of neuropsychiatric symptoms, symptoms of cognitive impairment, and dependence to others. As expected, those with dementia had higher levels of functional disability/limitations. Future research may examine whether functional disability/limitations predicts incident MCI or dementia in cognitively normal individuals.